PENGARUH PENGUNGKAPAN LIKUIDITAS, SOLVABILITAS, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Dwi Novita Komalasari; Yulazri Yulazri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
The purpose of this research is to examine the value of the company which is influenced by liquidity, solvency, company size, and profitability. The data source implemented in the research is a secondary data source of quantitative type and applies a causality research design. The technique applied to select sample objects from the population in the form of companies engaged in the energy sector for the period 2018-2021 listed on the Indonesia Stock Exchange (IDX) is a purposive sampling technique and the number of samples used is 19 companies with 76 sample data. Then testing the hypothesis in the research applies multiple linear regression analysis techniques. Based on the test, the following results are obtained, first, partially the firm value variable is positively influenced by liquidity. Then the second, partially the company value is positively influenced by solvency. Furthermore, the third, partially the company value is negatively affected by company size, and the fourth, the company value is partially positively influenced by profitability. Then the last one simultaneously the firm value variable is positively influenced by liquidity, solvency, firm size and profitability